The Management of Cleft Lip and Palate in Four Siblings with Van Der Woude Syndrome in a Developing Country: A Case Report - Mendy Hatibie Oley; Maximillian Christian Oley; Yudhaputra Setiadhi; Vania Sukarno; Deborah Florencia Gunawan; Muhammad Faruk (Jurnal Plastik Rekonstruksi, 2025)
Introduction: Van der Woude syndrome (VWS) is a rare genetic disorder characterized by cleft lip and/or palate and congenital lower lip pits. It is an autosomal dominant condition with high penetrance, affecting 0.5-2% of all cleft lip/palate cases. VWS is caused by mutations in the IRF6 gene and is associated with hypodontia and dental anomalies. Lip pits, which can cause aesthetic or functional problems, may intermittently drain saliva. VWS is diagnosed using genetic testing and bioinformatics tools, providing more accurate predictions. Treatment requires multidisciplinary care, including surgical removal of lip pits and cleft correction. This study describes a rare case of VWS family, including management strategies in low resource settings.Case presentation: A 42-year-old man from a non-consanguineous marriage presented with four out of five children affected by VWS, characterized by cleft lip and palate. All four children underwent labioplasty. The family history revealed no congenital defects in the father's and the first wife’s lineage, except for the second wife.Conclusion: Early identification of familial patterns and clinical presentation is essential in Van der Woude Syndrome, as it significantly impacts the management and quality of life of affected individuals, particularly in resource-limited settings.